APPLIED PHILOSOPHY IN EMPOWERING THE GIRL CHILD: FOSTERING INNOVATIVE LEADERSHIP, TECHNOLOGIES, AND DISCIPLINE FOR SOCIAL CHANGE - Ngogi Emmanuel Mahaye, (International Journal of Innovative Technologies in Social Science, 2025)
This research explores the intersection of innovation, technologies, leadership, and discipline in shaping the empowerment of the girl child. Focusing on the application of philosophical principles, the study aims to examine how these concepts can be utilized as catalysts for social change and empowerment. The study applies a desktop analysis methodology to gather, evaluate, and synthesize relevant literature on the role of innovation and leadership in fostering opportunities for young girls in education, technology, and social engagement. With the rapid development of innovation and artificial intelligence (AI), new opportunities exist for addressing these challenges through proactive and supportive disciplinary systems. It explores how discipline and leadership, underpinned by an applied philosophical framework, can guide the development of a more inclusive and sustainable society. Findings suggest that fostering a balance of innovation, leadership, and discipline can significantly enhance the potential of the girl child in the 21st century. This research provides practical recommendations for stakeholders, including educators, policymakers, and activists, to ensure that these forces are harnessed effectively for the girl child’s empowerment.Keywords: Girl Child, Innovation, Technologies, Leadership, Discipline, Applied Philosophy, Empowerment, Social Change, Gender Equality, Artificial Intelligence